Applications of social theories of learning in health professions education programs: A scoping review - Mukhalalati, Banan; Elshami, Sara; Eljaam, Myriam; Hussain, Farhat Naz; Bishawi, Abdel Hakim (Frontiers in Medicine, 2022)
Abstract Introduction: In health professions education (HPE), acknowledging and understanding the theories behind the learning process is important in optimizing learning environments, enhancing efficiency, and harmonizing the education system. Hence, it is argued that learning theories should influence educational curricula, interventions planning, implementation, and evaluation in health professions education programs (HPEPs). However, learning theories are not regularly and consistently implemented in educational practices, partly due to a paucity of specific in-context examples to help educators consider the relevance of the theories to their teaching setting. This scoping review attempts to provide an overview of the use of social theories of learning (SToLs) in HPEPs. Method: A scoping search strategy was designed to identify the relevant articles using two key concepts: SToLs, and HPEPs. Four databases (PubMed, ERIC, ProQuest, and Cochrane) were searched for primary research studies published in English from 2011 to 2020. No study design restrictions were applied. Data analysis involved a descriptive qualitative and quantitative summary according to the SToL identified, context of use, and included discipline. Results: Nine studies met the inclusion criteria and were included in the analysis. Only two SToLs were identified in this review: Bandura’s social learning theory (n= 5) and Lave and Wenger’s communities of practice (CoP) theory (n= 4). A total of five studies used SToLs in nursing programs, one in medicine, one in pharmacy, and two used SToLs in multi-disciplinary programs. SToLs were predominantly used in teaching and learning (n= 7), with the remaining focusing on assessment (n= 1) and curriculum design (n= 1). Conclusions: This review illustrated the successful and effective use of SToLs in different HPEPs, which can be used as a guide for educators and researchers on the application of SToLs in other HPEPs. However, the limited number of HPEPs that apply and report the use of SToLs suggests a potential disconnect between SToLs and educational practices. Therefore, this review supports earlier calls for collaborative reform initiatives to enhance the optimal use of SToLs in HPEPs. Future research should focus on the applicability and usefulness of other theories of learning in HPEPs and on measuring implementation outcomes.